2011
DOI: 10.1007/s10620-011-2006-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypothyroidism in Nonalcoholic Fatty Liver Disease

Abstract: Background A possible association between nonalcoholic fatty liver disease (NAFLD) and hypothyroidism has been suggested. Possible explanations for this association are the recognized links between hypothyroidism and various elements of the metabolic syndrome which is often present in NAFLD. To further explore this association, we determined the prevalence of hypothyroidism in a cohort of patients with NAFLD and analyzed the potential factors associated with hypothyroidism in this patient population. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
135
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 52 publications
3
135
1
3
Order By: Relevance
“…Although the authors appropriately matched the postmenopausal status, another possible confounder could have been the role of thyroid disorders in women. As recently shown ( 20 ), there is an increased prevalence of hypothyroidism in patients with NAFLD compared with controls without NAFLD ( 20 ). Th e association between NAFLD and hypothyroidism was stronger in women than in men.…”
mentioning
confidence: 73%
“…Although the authors appropriately matched the postmenopausal status, another possible confounder could have been the role of thyroid disorders in women. As recently shown ( 20 ), there is an increased prevalence of hypothyroidism in patients with NAFLD compared with controls without NAFLD ( 20 ). Th e association between NAFLD and hypothyroidism was stronger in women than in men.…”
mentioning
confidence: 73%
“…The prevalence of hypothyroidism among a cohort of 246 patients with biopsy-proven NAFLD was 21 vs 9.5% in 430 age-, gender-, race-and BMI-matched controls (90). In addition, the prevalence of hypothyroidism in patients with NASH is higher than those with more benign disease (90,91). There are currently no published studies that have examined NAFLD in the context of hyperthyroidism.…”
Section: Thyroidmentioning
confidence: 99%
“…Although some studies have reported associations of SCH with insulin resistance (7,8), metabolic syndrome (MS) (7,9), and CHD (10,11), not all previous findings have been consistent (12,13,14). Recent studies in adults (9,15,16) and children (7) have shown that SCH is closely associated with NAFLD independent of potential confounders. Based on these findings and considering that insulin resistance is a key feature of NAFLD, we hypothesized that the relationship of SCH with cardiometabolic risk factors and CHD may be influenced by the presence of increased intrahepatic fat.…”
mentioning
confidence: 99%